Perubahan pengetahuan dan praktek sadari setelah edukasi melalui whatsapp pada siswi SMAN Negeri 7 Banda Aceh - Nurdahliana, Nurdahliana; Dewi, Meliani Sukma; Henniwati, Henniwati (Poltekkes Kemenkes Aceh, 2025)
Background: Breast self-examination/SADARI is performed by young women who have experienced physical changes and secondary sexual development. Puberty occurs at the age of 12-13 years when breast enlargement occurs. SADARI should be performed on the 7th to 10th day of the menstrual cycle, as the low levels of estrogen and progesterone hormones prevent breast tissue from becoming edematous, making it easier to detect tumors or abnormalities during palpation.Objective: To determine the effect of WhatsApp (WA) audio-visual content on knowledge and practice of SADARI among female students at SMAN 7 in Banda Aceh City.Method: Quasi-experimental design using a pretest-posttest one-group design with two measurements: before and after the intervention with a single group of subjects. The sample consisted of the entire population, namely Grade 11 students who met the inclusion criteria. The sampling technique was purposive sampling, and analysis was conducted using a t-test.Results: After statistical testing showed a p-value of 0,000, indicating a significant difference in knowledge and skills among female adolescents after viewing the WhatsApp (WA) Audio Visual on SADARI.Conclusion: Female adolescents can perform SADARI regularly. Schools can form peer groups to share the knowledge gained about SADARI during the research process with younger students.